Assessment of the role of fuel and energy resources in ensuring the energy security of Kazakhstan - Daribekov, S.S.; Daribekova, A.S.; Yeskerova, Z.A.; Akhmetova, A.S. (BUKETOV BUSINESS REVIEW, 2019)
This article is devoted to the assessment of the role of fuel and energy resources of energy security in Kazakhstan. At the same time, the definitions of «energy security» are considered, the structure of the fuel and energy resources of the country, which are important for the state, is evaluated by various indicators that are strategically important for the development of the state’s economy. Promotion of the country’s economy is impossible without modernization of the existing technology, which allows to increase the efficiency of fuel and energy resources not by percent, but by several times due to utilization of losses and involvement of renewable energy sources in the turnover. The main problem is that the concept of its provision goes beyond the uninterrupted supply of energy resources for the needs of the economy, the world community has faced fundamentally new problems that require a change in traditional approaches to ensuring the energy security of the country.